2019
DOI: 10.2174/1574884714666181203095437
|View full text |Cite
|
Sign up to set email alerts
|

Role of Muscarinic Acetylcholine Receptors in Breast Cancer: Design of Metronomic Chemotherapy

Abstract: Background: muscarinic acetylcholine receptors (mAChRs) have attracted interest as targets for therapeutic interventions in different illnesses like Alzheimer´s disease, viral infections and different tumors. Regarding the latter, many authors have studied each subtype of mAChRs, which seem to be involved in the progression of distinct types of malignancies. Methods: We carefully revised research literature focused on mAChRs expression and signaling as well as in their involvement in cancer progression and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…The production of ACh by tumor cells and the subsequent interaction with muscarinic receptors frequently activate an autocrine/paracrine loop, modulating cell proliferation, migration and angiogenesis [ 23 ]. Several studies have largely reported the involvement of muscarinic receptors in several primary and metastatic tumors, such as colon [ 24 , 25 ], ovary [ 26 ], prostate [ 27 , 28 , 29 ], lung [ 30 , 31 ] and breast carcinoma [ 32 , 33 , 34 , 35 ], melanoma [ 36 ] and in glioblastoma, as demonstrated by our group [ 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 60%
“…The production of ACh by tumor cells and the subsequent interaction with muscarinic receptors frequently activate an autocrine/paracrine loop, modulating cell proliferation, migration and angiogenesis [ 23 ]. Several studies have largely reported the involvement of muscarinic receptors in several primary and metastatic tumors, such as colon [ 24 , 25 ], ovary [ 26 ], prostate [ 27 , 28 , 29 ], lung [ 30 , 31 ] and breast carcinoma [ 32 , 33 , 34 , 35 ], melanoma [ 36 ] and in glioblastoma, as demonstrated by our group [ 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 60%
“…Considering the latter, together with our previous findings in MCF-7 cells that were sensible to a low dose metronomic therapy focused on muscarinic receptors [16] we designed a metronomic administration of PX plus muscarinic agonists at low concentrations. This strategy, besides focusing on muscarinic receptors as novel targets for the treatment of TN tumors, could be less aggressive for normal mammary cells that lack of these receptors [2,12]. Moreover, our results reveal the possibility of generalizing the usage of this combination of drugs since it is also effective when PX is replaced by doxorubicin.…”
Section: Plos Onementioning
confidence: 75%
“…Breast cancer is still the most frequent type of malignancy in women and represents a major and unsolved problem for public health [ 1 , 2 ]. Luminal and triple negative (TN) represent the two opposite ends of the molecular classification of breast tumors and they thoroughly differ regarding treatment and patients´survival [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the factors involved in the carcinogenesis process is acetylcholine and its receptors, both muscarinic and nicotinic. Their expression has been demonstrated in numerous types of cancer cells [19][20][21]. It has also been proven that these cells contain acetylcholinesterase (AChE), an enzyme that enables cells to produce ACh in the absence of agonists from the external environment.…”
Section: Aacetylcholine (Ach) and Its Receptorsmentioning
confidence: 99%